2008
DOI: 10.1007/s11524-008-9266-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Education of Adolescents with Asthma in an Urban School District: Results from a Large-scale Asthma Intervention

Abstract: Asthma is a leading cause of hospitalizations, acute care utilization, health care costs, and school absences in children. Asthma morbidity is disproportionately high in inner city populations. In general, community-based public health interventions to reduce asthma morbidity have had modest success due in part to their limited reach and low participation by the targeted population. Adolescents have been especially difficult to reach. A coalition of community organizations developed a school-based, population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…Each child should then be individually managed to ensure that their specific needs are addressed, through a partnership between the child's doctor, parents and school staff (9). A model for 'asthma friendly schools' has been described (28).…”
Section: Challenges For the Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Each child should then be individually managed to ensure that their specific needs are addressed, through a partnership between the child's doctor, parents and school staff (9). A model for 'asthma friendly schools' has been described (28).…”
Section: Challenges For the Schoolmentioning
confidence: 99%
“…Encourage full participation in physical activities when students are well, offer reduced/modified activities if experiencing symptoms. There are many examples of successful education programmes for school children with asthma which incorporate some of the above-mentioned principles (28)(29)(30)(31).…”
Section: Challenges For the Schoolmentioning
confidence: 99%
“…Most school-based educational programs have focussed on building skills for elementary school-aged children and have demonstrated improvements in asthma knowledge, confidence/self-efficacy, asthma management skills and associated asthma morbidity outcomes, such as improved quality of life, and reduced symptoms, emergency department visits, urgent care visits, hospitalizations and school absenteeism. [46][47][48][49][50] Studies in adolescents, an identified difficult-to-reach group, have demonstrated acceptance, involvement and retention by this age group: over 75% of those eligible participated and over 70% were retained. 37,38,44,45 Recently, school-centered asthma education efforts have targeted adolescents of low income living in urban settings.…”
Section: Interventions To Improve Asthma Self-management Skillsmentioning
confidence: 99%
“…To address the specific asthma-related needs of the middle school population, Oakland Kicks Asthma, a large community-based intervention in Oakland, California, developed an asthma management education program for students in the Oakland Unified School District (OUSD), a diverse, predominantly low-income urban school district with high asthma prevalence 7,19. Known as Kickin’ Asthma , this curriculum for sixth-grade students with asthma teaches management strategies with an emphasis on appropriate medication use.…”
Section: Introductionmentioning
confidence: 99%